Continuity and changes in grandchild care and the risk of depression for Chinese grandparents: new evidence from CHARLS - Hong, Yue; Xu, Wei (Frontiers in Public Health, 2023)
Objectives Although studies have researched the mental effects of intergenerational care, little is known about the impact of transformations in caregiving intensity on depression. This study explores grand-parents’ depressive symptom outcomes in terms of changes over time in grandparental childcare, with considerations for subgroup differences. Method Using data from the 2015–2018 China Health and Retirement Longitudinal Study on grandparents aged 45 and older, we adopted generalized estimating equations to estimate the effects of seven category changes [(1) continued to provide high-intensity or (2) low-intensity care at both waves; (3) never provided care; (4) started caregiving; (5) ended caregiving; (6) provided less intensive care; and (7) provided more intensive care] over time in grandparental childcare on depressive symptoms among 17,701 grandparents with at least one grandchild, as well as how the impact varies by gender and urban/rural areas. Results Grandparents who decreased the intensity of care, stopped childcare, or offered continuous low-intensity care were associated with a lower level of depression compared with those providing no childcare. In addition, the benefit of continuous caregiving on mental health was especially noticeable in urban grandmothers. Conclusion Providing continuous low-intensity, decreased-intensity grandparenting and the cessation of caregiving were associated with a decreased level of depression for Chinese grandparents; however, there were complex interactions at play. Policies aimed at supporting grandparenting should consider caregiving intensity transitions relevant to gender and urban/rural residence.